1964
DOI: 10.1099/00221287-35-3-391
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of DNA Uptake by Haemophilus influenzae

Abstract: SUMMARYThe rates of formation of transformed cells in mixtures of transforming DNA and transformable HaemophiZus inJuenxae bacteria have been measured. The data were interpreted as follows. About 4-5 sec. are required for the penetration of a DNA particle of 8-9 x 106 mean molecular weight. The average number of penetration sites per bacterium is probably two. There is no reversible attachment of DNA to these sites. Crude calculations show that about one out of every two encounters between a bacterium and a DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1968
1968
1994
1994

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…Our basic strategy has been to find a selective inhibitor or experimental condition that would allow normal DNA binding to the cells, but would prevent the nuclease-resistant association between molecules and cells and would also prevent genetic transformation. Published observations suggested that the appearance of nuclease-resistant form of DNA was an energy requiring process (1,5,(7)(8)(9)(10). Table 1 shows that, indeed, several inhibitors of cellular energy metabolism cause a greater decrease in the nuclease-resistant fraction of cell-associated DNA than in the total amount of DNA bound.…”
Section: Resultsmentioning
confidence: 99%
“…Our basic strategy has been to find a selective inhibitor or experimental condition that would allow normal DNA binding to the cells, but would prevent the nuclease-resistant association between molecules and cells and would also prevent genetic transformation. Published observations suggested that the appearance of nuclease-resistant form of DNA was an energy requiring process (1,5,(7)(8)(9)(10). Table 1 shows that, indeed, several inhibitors of cellular energy metabolism cause a greater decrease in the nuclease-resistant fraction of cell-associated DNA than in the total amount of DNA bound.…”
Section: Resultsmentioning
confidence: 99%
“…Uptake of DNA by other transformable bacteria also requires energy (16)(17)(18), but it is not known whether the energy is required for the initial binding reaction. Donor DNA is also converted to single strands (7,8) and external fragments (3) in B. subtilis, so its entry mechanism may also involve DNase action.…”
Section: Discussionmentioning
confidence: 99%
“…Donor DNA is also converted to single strands (7,8) and external fragments (3) in B. subtilis, so its entry mechanism may also involve DNase action. Haemophilus influenzae presents a different pattern: there is a rapid, energy-dependent uptake of DNA into a DNase-resist-ant form (18), but this DNA remains double stranded (19,20). At a much slower rate donor DNA fragments appear outside the cell (19) and single-stranded segments are inserted into recipient DNA (20).…”
Section: Discussionmentioning
confidence: 99%
“…or washing ( 11). 3 The early stages .of transformation (12,13,14,15) are kinetically similar to phage adsorption (16). That is, the interaction between DNA and a recipient cell results from random collisions, followed by reversible binding of the DNA to the cell, and irreversible binding.…”
Section: Recovery Ofmentioning
confidence: 99%